Adaptation and Observation Trial of the Influence of Three Composts on the Yield of Carrot (Daucos Carota L.) Under The Agro-Ecological Conditions of Gbadolite in the Democratic Republic of Congo - Molongo Mokondande Médard; Ngalakpa Ziada Héritier; Mbaya Isaac; Nzolowa Banze Francis; Muhammad Ridwan (Budapest International Research and Critics University, 2023)
The aim of the present study was to initiate an adaptation trial and observe the influence of three composts on carrot yield under the agro-ecological conditions of Gbadolite. The experimental design adopted was that of randomized complete blocks with 4 treatments distributed over 3 replications. The total area of the experimental field was 28.8 m2, i.e. 8 m long and 3.6 m wide. Each elementary plot had an area of 2.4 m², i.e. 2 m long and 1.20 m wide. The distance between the blocks was 0.50 m and the plots were also 1.00 m apart. Treatments were as follows: T0: Unamended control plot; T1: Bursary; T2: Chromolaena+legume amendment; T3: Chromolaena+grass amendment. Each treatment was amended with 15kg of compost per bed following the composts. Final planting was carried out at 0.15 m x 0.40 m spacing, with one plant per stake, i.e. a density of 30 plants per plot of 2.4 m2 each. The plot enriched with dung compost yielded 16.75 t/ha (T3); the plot amended with C. odorata + grasses yielded 14.25 t/ha; the plot amended with C. odorata + legume mulch yielded 13.33 t/ha; and the control plot yielded 8.17 t/ha. Carrot cultivation is therefore feasible in the agro-ecological conditions of gbadolite.